The Moderating Role of Board Independent in Managerial Ownership and Firm Value: Evidence in Indonesia - Perwito, Perwito; Nugraha, Nugraha; Mayasari, Mayasari; S, Yayat (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
This study aims to empirically assess the conditional effect of managerial ownership on the firm value moderating role of the independent board. Using a sample of Indonesian listed firms from 2015-2020 and panel data of 2,627, we used PROCESS V3.4. for SPSS to estimate research models. Research findings; there is a non-linear relationship between the effect of managerial ownership on firm value, in line with the entrenchment hypothesis. Furthermore, the findings of this study indicate that the independent board does not provide a moderating effect on the relationship, but the independent board is a predictor of firm value. The critical implications are; It enriches existing knowledge of agency theory by emphasizing the importance of the involvement of an independent board. A new perspective in the conditional effect analysis of management ownership on firm value, moderated by the role of an independent board. Keywords:  managerial ownership, independent boards, firm value, the moderation effect